Development Of Animated Video Media On Early Childhood Speaking Skills At Nurul Jannah Kindergarten Palembang - Oktafiana, Insyira'ah; Syarifuddin; Dwi Andika, Windi (ATTA`DIB, 2025)
This research is in the background by the low speaking ability of early childhood to learning to take place. The learning media used by educators tends to be monotonous and less interesting for children and less interactive so that children's interest in learning is reduced to pay attention to learning. The media used is not attractive, making children quickly bored in the learning process. This study aims to analyze the needs for the development of animated video media on early childhood speaking skills in Nurul Jannah Kindergarten Palembang Kindergarten. The method used was qualitative descriptive with interview techniques and questionnaires to 2 educators and 12 children at Nurul Jannah Kindergarten Palembang. The results of the study show that educators experience obstacles in the use of learning media for early childhood, interaction with children is slightly hampered because learning is not interesting. Meanwhile, children show a high interest in animated video media, attracting responses in learning between teachers and children, communicative language, and interesting technology-based learning. The needs analysis shows that the development of animated video media for early childhood speaking skills at Nurul Jannah Palembang Kindergarten is an effective medium in creating good learning for children, contextual, and humanist for early childhood so as to create reciprocity between teachers and children in carrying out learning in the classroom